“As a Shadow” – the Experiences of a Support Teacher of Students With Autism Spectrum Disorders (ASD) - Danuta Kądziołka (Horyzonty Wychowania)
RESEARCH OBJECTIVE: The objective of this article is to explore the experiences, challenges, and pedagogical strategies employed by teachers who co-facilitate the education of students with Autism Spectrum Disorder (ASD).